COMPENSATION AND ABSOLUTE LIABILITY PRINCIPLE ON THE CASE OF AIR ASIA QZ 8501 AIRPLANE ACCIDENT 2014 - Nurul Alifah Jovita; Rosmawati Rosmawati (Student Journal of International Law, 2021)
This study investigates the issue of compensation based on the absolute responsibility principle in the Air Asia QZ 8501 airplane accident in 2014. This study uses normative juridical legal research with secondary data as primary data obtained through literature study. The results indicate a lack of clarity in the implementation of compensation as regulated in the National Aviation Law regarding the maximum amount of time required in insurance claims toward the heirs. Without a precise time limit, airlines and insurance companies will create many obstacles during the data collection process and the documents involved. It is recommended that the government strengthen the rules regarding the provisions in implementing compensation, especially related to the insurance claim process toward the heirs. In addition, it is also recommended for airlines and insurance companies to consistently set a precise time limit for the investigation and identification of the victims to speed up the issuance of the necessary documents from the Court. Keywords: Airplane Accident, Compensation, International Air Freight, Principle of Liability, Strict Liability.